2004
DOI: 10.1042/bst0320485
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Sterile20-like kinase 1 and the regulation of apoptosis

Abstract: Mammalian Sterile20-like kinase 1 (Mst1) is a ubiquitously expressed serine/threonine kinase which represents a member of the rapidly expanding family of enzymes related to the yeast Sterile20 kinase. Although the physiological function of Mst1 and its role in intracellular signalling is still unclear, reports to date suggest that Mst1, similar to its yeast homologue, operates in the MAPK (mitogen-activated protein kinase) pathway and, in this capacity, may represent a putative MAPK kinase kinase kinase. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 40 publications
(96 reference statements)
4
49
0
Order By: Relevance
“…Mst1 has been reported, in response to a wide variety of apoptotic stimuli, to be a prominent stimulator during apoptosis [27], playing an important role as a caspase effector that contributes to apoptosis. Mst1 has also been shown to act upstream of MAPK kinase kinase (MAPKKK) that regulates p38 and JNK activities, acting as a putative MAPK kinase kinase kinase (MAPKKKK) [19], thus, functioning in a positive feedback pathway that amplifies the apoptotic response through MAPK activation. However, the biological significance of MAPK activation has been emphasized for only its apoptotic effects, in spite of being known to have anti-apoptotic effects as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mst1 has been reported, in response to a wide variety of apoptotic stimuli, to be a prominent stimulator during apoptosis [27], playing an important role as a caspase effector that contributes to apoptosis. Mst1 has also been shown to act upstream of MAPK kinase kinase (MAPKKK) that regulates p38 and JNK activities, acting as a putative MAPK kinase kinase kinase (MAPKKKK) [19], thus, functioning in a positive feedback pathway that amplifies the apoptotic response through MAPK activation. However, the biological significance of MAPK activation has been emphasized for only its apoptotic effects, in spite of being known to have anti-apoptotic effects as well.…”
Section: Discussionmentioning
confidence: 99%
“…Mst1 (mammalian sterile 20-like kinase 1) is a ubiquitously expressed serine/threonine kinase having a molecular weight of 59 kD [19]. It is a mammalian homolog of the budding yeast Ste20 kinase [20].…”
Section: Introductionmentioning
confidence: 99%
“…MST1 and MST2 are mammalian sterile20-like kinases and are supposed to be involved in the induction of apoptosis (de Souza and Lindsay, 2004). TTK is known to function in the spindle checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinases generally have key roles in signal transduction driven by various stimuli (Karin and Hunter, 1995). For example, mammalian Ste20-like kinase-1 (MST1) is a Ser/Thr kinase that is activated by apoptosis-inducing stimuli (de Souza and Lindsay, 2004). Lehtinen et al (2006) reported that MST1 is activated by H 2 O 2 and induces cell death by phosphorylating the transcription factor FOXO in primary mammalian neurons.…”
Section: Introductionmentioning
confidence: 99%